Vacuum‐Powered Soft Pneumatic Twisting Actuators to Empower New Capabilities for Soft Robots. Issue 1 (29th October 2018) - Jiao, Zhongdong; Ji, Chen; Zou, Jun; Yang, Huayong; Pan, Min
Abstract: Vacuum‐powered soft pneumatic actuators (V‐SPAs) are a promising enabling technology for a wide range of emerging applications, including artificial muscles, programmable locomotion, and flexible grippers. This is due to their flexible deformation, clean power supply, safe interaction with users, and high reliability compared with alternative actuators. A new vacuum‐powered soft pneumatic twisting actuator (V‐SPTA) is designed, which has a single seamless chamber and is completely soft, with no rigid frames. The actuator has two degrees of freedom (DoFs) and offers the advantages of diverse functions, ease of manufacture, high load capability, and is cost efficient. Their potential to achieve linear, twisting, and radial movements is shown by employing different combinations of V‐SPTAs. The feasibility of the V‐SPTA is demonstrated using prototypes based on flexible joint and wrist, rotating crawling robot, pipe‐climbing robot, and V‐SPTAs‐driven car. The V‐SPTA successfully enhances the capability of existing V‐SPAs by providing an important additional DoF. The work therefore expands the capability of soft robots while minimizing the complexity of actuator design and reducing the manufacturing cost. Abstract : A novel vacuum‐powered soft pneumatic actuator that operates with two degrees of freedom offers the advantages of diverse functions, ease of manufacture, high load capability, and is cost efficient. The feasibility of the actuator is demonstrated using prototypes based on a flexible joint and wrist, a rotatable crawling robot, a pipe‐climbing robot, and a vacuum‐powered soft pneumatic twisting actuator‐driven car.